Quantum fluctuation theorem in an interacting setup: point contacts in fractional quantum hall edge state devices - Komnik, Andreas; Saleur, Hubert (Physical review letters, 2011)
We verify the validity of the Cohen-Gallavotti fluctuation theorem for the strongly correlated problem of charge transfer through an impurity in a chiral Luttinger liquid, which is realizable experimentally as a quantum point contact in a fractional quantum Hall edge state device. This is accomplished via the development of an analytical method to calculate the full counting statistics of the problem in all the parameter regimes involving the temperature, the Hall voltage, and the gate voltage.
Gesehen am 06.07.2022